Role of CRRT (Continuous Renal Replacement Therapy) as Management of Cardiac Arrest Patient with Postpartum Acute Lung Edema and Cardiomyopathy in the ICU - Anwary, Army Zaka; Indriasari (Journal of Society Medicine, 2023)
Introduction: Continuous renal replacement therapy (CRRT) is a type of renal replacement therapy commonly used in the ICU for hemodynamically unstable patients. CRRT can comprehensively achieve various goals such as reducing inflammatory mediators, alleviating fluid overload, and correcting acidosis. Therefore, whether CRRT is necessary and when to initiate CRRT are basic questions that intensivists must consider when treating critical patients in the ICU to achieve favorable outcomes. Method: This retrospective case report analyzed patient clinical data. The patient provided written informed consent to publish their case details and accompanying images. Results: We present the case of a 23-year-old woman with acute pulmonary edema and peripartum cardiomyopathy who experienced cardiac arrest prior to cesarean section. Postoperatively, the patient was admitted to the ICU, and CRRT was initiated to correct various complications. During treatment, the patient experienced clinical improvement and improvement in respiratory and renal function parameters until she was discharged from the ICU without neurological deficits. Conclusion: Early assessment, the decision to use CRRT, and comprehensive therapy are crucial for the successful treatment of post-cardiac arrest patients with pregnancy-related acute pulmonary edema and peripartum cardiomyopathy in the ICU.